2015
DOI: 10.1016/j.jrras.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Extension shelf life of batte by using hydrocolloids and gamma irradiation

Abstract: Available online xxxKeywords: Shelf lifeBatte Hydrocolloids Irradiation a b s t r a c t Batte (is baked french) one of the most baked coated most prevalent in the markets after the cake wrapping. Batte exposed generally two types of corruption which is occurring phenomenon of (anti-staling) and corruption microbial (molds). In this study produced batte with an attempt to prolong the period of its validity by addition 1.5% hydrocolloids, (which is 0.5% sodium alginate, 0.5% k-carrageenan and 0.5% hydroxyl propy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
0
0
Order By: Relevance
“…Similar results were also showed that 2.5 kGy of -irradiated bamboo shoots maintained the quality capable of long storage periods [30]. The utmost reduction in the bacterial population is mainly due to the direct or indirect effects of irradiation on the microorganisms as reported in various conducted research studies [31][32][33][34][35].…”
Section: Microbiological Population Effectsupporting
confidence: 79%
“…Similar results were also showed that 2.5 kGy of -irradiated bamboo shoots maintained the quality capable of long storage periods [30]. The utmost reduction in the bacterial population is mainly due to the direct or indirect effects of irradiation on the microorganisms as reported in various conducted research studies [31][32][33][34][35].…”
Section: Microbiological Population Effectsupporting
confidence: 79%